ANALISIS BREAK EVENT POINT (BEP) SEBAGA ALAT PERENCANAAN PENJUALAN PADA TINGKAT LABA YANG DIHARAPKAN (Studi Kasus PTPN VII Unit Bekri Tahun 2016-2018) - Anggie Restu Noviana (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2020)
The method used by researchers is the Quantitative Analysis method. Data collection techniques based on literature study, field studies, and interviews. The analytical tool used in this study is Break Event Point (Break-even Point), Contribution Margin Ratio (comparison of income from sales difference and variable costs represented), Margin Of Safety (safety limit). Analysis Results from the discussion, Calculation of Break Event Point (BEP) before determining Profit at PTPN VII Bekri Unit, Central Lampung in 2016 Palm Oil production reached Break Event Point (BEP) of Rp. 28,515,678,884 or at the time of sale 3,738,501 kg. and for Palm Oil production of Rp. 835,512,136 and at the time of sale 231,711 kg. In 2017 Palm Oil production reached a Break Event Point of Rp. 17,538,148,989 and at the time of sales 2,722,395 kg, and at the production of palm kernel oil Rp. 769,526,689 and at the time of sale 194,096 kg. In 2018 palm oil production will reach Rp. 103,144,553,486 and at the time of the sale of 16,001,461 kg. and for palm kernel oil production of Rp. 1,517,966,631 and at the time of sale 419,542 kg. Can also be known Break Event Point (BEP) after Determination of Profit on Palm Oil Production in 2016 amounting to Rp. 21,573,659,680 or 2,502,746 kg, in 2017 Rp. 18,453,624,090 or 2,090,759 kg, and in 2018 the amount of Rp. 73,391,316,904 or 10,990,240 Kg. Break Event Point (BEP) after Determination of Profit on Palm Oil Production in 2016 amounting to Rp. 827,479,773 or 200,644 kg, in 2017 amounting to Rp. 764,614,817 or 175,816 kg, and in 2018 the amount of Rp. 1,294,093,854 or 305,397 kg.